Inflammation as the nexus: exploring the link between acute myocardial infarction and chronic obstructive pulmonary disease - Marriott, Eloise; Singanayagam, Aran; El-Awaisi, Juma (Frontiers in Cardiovascular Medicine, 2024)
Chronic obstructive pulmonary disease (COPD), particularly following acute exacerbations (AE-COPD), significantly heightens the risks and mortality associated with acute myocardial infarction (AMI). The intersection of COPD and AMI is characterised by a considerable overlap in inflammatory mechanisms, which play a crucial role in the development of both conditions. Although extensive research has been conducted on individual inflammatory pathways in AMI and COPD, the understanding of thrombo-inflammatory crosstalk in comorbid settings remains limited. The effectiveness of various inflammatory components in reducing AMI infarct size or slowing COPD progression has shown promise, yet their efficacy in the context of comorbidity with COPD and AMI is not established. This review focuses on the critical importance of both local and systemic inflammation, highlighting it as a key pathophysiological connection between AMI and COPD/AE-COPD.